R&D investment and financial performance in EU countries: The role of shareholder protection and creditor rights in renewable energy firms - Karlilar, Selin; Tarzibashi, Omar Fikrat Fateh (Springer Heidelberg, 2023)
Renewable energy sources have become a priority for countries' energy agendas due to climate change. Accordingly, the financial performance of renewable energy firms should be enhanced through research and development (R&D) investment to achieve the energy transition. The positive effect of R&D investment on financial performance is well documented in the literature. However, it is not clear whether this positive effect varies or not depending on the institutional characteristics of countries, such as shareholder protection and creditor rights. This study examines whether shareholder protection, on the one hand, and creditor rights, on the other, have any moderating effect on the R&D-financial performance nexus by using firm-level data from 912 renewable energy firms in 21 European Union countries from 2011 to 2020. The results show that shareholder protection strengthens the positive effect of R&D investment on the financial performance of renewable energy firms, while creditor rights negatively moderate this relationship. Thus, firms operating in countries with strong shareholder protection (creditor rights) invest more (less) in R&D activities, which leads to an increase (decrease) in financial performance. Consequently, policymakers may consider policy changes that encourage shareholders and discourage creditors from maximizing their R&D investments, which increase financial performance.
Keywords: R&D investment; Shareholder protection; Creditor rights; Financial performance; Renewable energy firms